Luliconazole Loaded Niosomal Topical Gel: Factorial Design, in vitro Characterization and Antifungal Study - Shah, Nirmal; Prajapati, Rahul; Gohil, Dipti; Aundhia, Chintan; Sadhu, Piyush; Kardani, Sunil (Indian Journal of Pharmaceutical Education and Research, 2023)
Aim/Background: This research work intended to make use of prospective advantages of niosomes for the improvement in topical delivery of poorly soluble luliconazole. Materials and Methods: Luliconazole, an anti-fungal agent used in the treatment of fungal infection, was successfully formulated as niosomal topical gel by using a polymer carbopol 934. The 32 full factorial statistical design was employed as a means for the optimization of niosomal formulation to check the impact of two formulation factors namely, concentration of cholesterol and span 60 on two dependent variables % drug release and % drug entrapment efficiency in formulated niosomal formulations. Results: The mean vesicular size, Zeta potential, drug release and entrapment efficiency of optimized formulation was found 150.6 ± 11.1 nm, -23.5 ± 5.08, 92.41 ± 2.44% and 92.36 ± 2.85%, respectively. The scanning electron microscopy study reveals that the optimized formulation was spherical, porous and rough in surface. The thermogram of differential scanning calorimetry study states that the drug may be solubilise or converted to amorphous form in niosomal vesicles. The viscosity and spreadability of niosomal gel were observed satisfactorily for the easy topical application. The ex vivo study of optimized niosomal gel showed significant higher drug release (97.31 ± 3.18%) in comparison with marketed product (82.20 ± 1.95%). The antifungal study showed considerable antifungal effectiveness of niosomal gel against the conventional marketed preparation. Conclusion: Henceforth, it can be concluded that the niosomes loaded topical gel of luliconazole may be useful for reducing the application frequency of conventional topical product and thereby improves the patient compliance.
Keywords: Poorly soluble drug; Nanocarrier; Topical application; Antifungal study